GENDER EQUALITY IN THE QUR'AN: IMPLICATIONS FOR SOCIAL JUSTICE EDUCATION - Ahmad Syarifudin; Romlah Abubakar Askar (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
One of the serious considerations in Islam pertains to the position of men and women. Islam highly values the worth of women. Gender equality is an essential topic to ensure that individuals, regardless of their gender, have equal opportunities, rights, and responsibilities in all aspects of life, while eliminating discrimination, violence, and harassment against women. Therefore, further discourse is necessary to rectify misconceptions. This research aims to explore the positions of both genders. It emphasizes that men and women share the same human status, having been created from the same substance, as ordained by God. The study employs qualitative research, specifically a literature review using relevant journals, books, and articles related to this topic.